Linear maps preserving G-unitary operators in Hilbert space - Abdellatif Chahbi; Samir Kabbaj (Arab journal of mathematical sciences, 2015)
Let H be a complex Hilbert space and B(H) the algebra of all bounded linear operators on H. We give the concrete forms of surjective continuous unital linear maps from B(H) onto itself that preserve G-unitary operators.